I am God - Sartori, Giacomo, 1958- (Restless Books, 2019)
Diabolically funny and subversively philosophical, Italian novelist Giacomo Sartori's I Am God is the diary of the Almighty's existential crisis that erupts when he falls in love with a human. And not just any human, but a geneticist and fanatical atheist who's certain she can improve upon the magnificent creation she doesn't even give him credit for. Which is frustrating, for a god.